Lobar or sublobar resection for stage I lung cancer: that is (still) the question! - Fiorelli, Alfonso; Loizzi, Domenico; Santini, Mario (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Lung cancer causes more than 1.4 million deaths annually (1). Surgery is the main treatment given with curative intent and lobectomy with lymph node resection is the standard procedure for early Stage of non-small-cell lung cancer (NSCLC), having a 5-year survival rates of up to 70% (2). This assumption is based on the results of the randomized controlled trial (RCT) reported by the Lung Cancer Study Group (LCSG) in 1995 (3). The authors compared overall survival of lobectomy versus limited resection (wedge resection and segmentectomy) for the management of Stage I NSCLC. They evaluated 495 patients with clinical stage IA NSCLC, of these 247 resulted to have a pathologic stage pIA. Limited resection compared to lobectomy presented a poorer 5-year survival rate (56% vs. 73%; P=0.06), a lower freedom from recurrence rate (62% vs. 78%, P=0.04), and three-fold increase in local recurrence rates (5.4% vs. 1.9%, P=0.009).